Comparative analysis of murabahah and musyarakah mutanaqisah contract in Islamic home financing ownership at Islamic bank : Case in BTN Syariah Surakarta - Agung Abdullah (NUsantara Islamic Economic Journal, 2022)
This research aims to determine the implementation of the murabahah contract and musyarakah mutanaqisah on ownership financing houses in Islamic Banks, as well as the use of musyarakah mutanaqisah contracts as financing product innovations house ownership with a qualitative method. The data in this study were obtained by interview,observation, and documentation. The data sources used are primary data and data secondary. Results from study proofs that the use of musyarakah mutanaqisah contract on home financing ownership in Islamic banks can be product innovation because its use is more flexible and can be used for various product financing. Whereas part big product home financing ownership in Islamic banks still uses a murabahah contract because of a fix installment. Otherwise, musyarakah mutanaqisah contract is an that should not be missed, although not familiar, this contract provides more benefits for the bank and convenience for the customer.